2023
DOI: 10.29121/granthaalayah.v11.i3.2023.5058
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Advanced Satellite Technology to Accelerate Man-Made Flash Floods

Abstract: There is no doubt that it is world-class innovative scientific research in advanced technology. This research on flood is unique, which will open many research doors for current and future generations. Rain falling from the sky to the earth is certainly a blessing for mankind but when a flash flood occurs with human controlled technology, it is painful for all. Studies have shown that the misuse of satellite technology has caused massive damage in man-made flash-floods, cyclones, tornadoes and other disasters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…As a result, due to the digital tracking of cyber criminals, the targeted individuals face problems in their daily life and get affected by the coronavirus disease Miah et al (2023e). These cybercriminals killed the researcher 's mother, mother-in-law, father-in-law, uncles, sisters-in-law, physicians, politicians, vets, pets, and pond-filled fish Miah et al (2021e), Miah et al (2021f), Miah et al (2021g), Miah et al (2023f), Miah et al (2023g). Ultimately, the study found that the coronavirus is spread by tracking through man-made sensor technology, but is not contagious.…”
Section: Challenging 24/7mentioning
confidence: 99%
“…As a result, due to the digital tracking of cyber criminals, the targeted individuals face problems in their daily life and get affected by the coronavirus disease Miah et al (2023e). These cybercriminals killed the researcher 's mother, mother-in-law, father-in-law, uncles, sisters-in-law, physicians, politicians, vets, pets, and pond-filled fish Miah et al (2021e), Miah et al (2021f), Miah et al (2021g), Miah et al (2023f), Miah et al (2023g). Ultimately, the study found that the coronavirus is spread by tracking through man-made sensor technology, but is not contagious.…”
Section: Challenging 24/7mentioning
confidence: 99%
“…Research shows that Bangladesh is unlikely to experience earthquakes, although some experts are predicting high-magnitude earthquakes in the region -either experts are wrong or cybercriminals are inciting falsehoods to spread fear among the public, according to the study. The researchers think that this innovative study will open the eyes of all conscious people, they will understand the main cause of excessive earthquakes, flash flood Miah et al (2023h), landslides and relevant man-made disasters around the world. The research shows that using advanced satellite technology, earthquakes can be created in time on any tectonic plate on Earth.…”
Section: Risks In Seismic Zonementioning
confidence: 99%
“…Myths about artificial earthquakes on Earth will be unmasked -but that day is not far off. Research shows that humans will mitigate artificial earthquakes with safe technology, that earthquake terrorists will be prosecuted in high courts Miah et al (2023); Miah et al (2023h); Miah et al (2022); Miah et al, 2022a), that an earthquake-free world will be peaceful -this is universal truth.…”
Section: Myth About Earthquakementioning
confidence: 99%
See 2 more Smart Citations